2008
DOI: 10.1088/0957-4484/19/25/255101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gold nanoparticles as the additive in real-time polymerase chain reaction with SYBR Green I dye

Abstract: Gold nanoparticles (AuNPs) have been proven to be able to improve the specificity or increase the efficiency of a polymerase chain reaction (PCR) when a suitable amount of AuNPs was used. However, there is still a lack of systematic evaluation of AuNPs in real-time PCR. In this study, DNA degradation and the fluorescence quenching effect of AuNPs were first tested in real-time PCR. Then two different kinds of Taq DNA polymerase, native and recombinant Taq polymerase, were employed to evaluate the AuNPs' effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
(39 reference statements)
0
26
1
Order By: Relevance
“…However, the concrete mechanism is not still clarified well. Li, et al also report that gold nanoparticles [22][23] can improve the efficiency or specificity of PCR and shorten reaction times, the excellent heat-transfer property of nanoparticles may be responsible for improving PCR efficiency [23][24]. However, so far few report is closely associated with the effects of quantum dots on real-time PCR.…”
Section: Open Accessmentioning
confidence: 99%
“…However, the concrete mechanism is not still clarified well. Li, et al also report that gold nanoparticles [22][23] can improve the efficiency or specificity of PCR and shorten reaction times, the excellent heat-transfer property of nanoparticles may be responsible for improving PCR efficiency [23][24]. However, so far few report is closely associated with the effects of quantum dots on real-time PCR.…”
Section: Open Accessmentioning
confidence: 99%
“…However, there have been a number of contradictory reports stating that gold nanoparticles have remarkably negative effects on PCR efficiency. Yang et al [8] reported that they could inhibit PCR efficiency at high levels of concentration, and suggested a complex interaction between gold nanoparticles and the Taq polymerase DNA synthetic enzyme. Vu et al [9] concluded that the surface interaction between gold nanoparticles and polymerase, rather than the DNA template or primers, inhibited PCR efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the conventionally used small molecular additives, such as formamide, 11 tetramethylammonium chloride 12 and its derivatives, 13 and betaine, 14 nanoparticles (NPs) have received considerable attention due to their unique physicochemical properties, which are significantly different from those of their bulk counterparts. Various NP systems, including nanogold, [15][16][17][18] carbon nanotubes (CNTs), 19 carbon nanopowder, 20 magnetic NPs, 21 semiconducting NPs, 22,23 and dendrimers 24 have been used as additives to improve the PCR specificity and efficiency. Nonspecific amplification problems can be overcome in the presence of NPs.…”
Section: Introductionmentioning
confidence: 99%